Nanotechnological Insights on Therapeutic Strategies for Diabetic Nephropathy - Balamurali Venkatesan; Pavithra Selvan; Natarajan V; Sakthinarenderan Saikumar; Naveenkumar Karuppasamy (Medical Research and Its Applications Vol. 3, 2024)
Diabetes Mellitus is the main cause of diabetic nephropathy (DN), a chronic illness which predominantly contributes to kidney failure. However, Dialysis is nonetheless required for end-stage renal failure, which is the more severe stage of diabetic kidney disease. Around 13-25% of individuals encounter this kind of disease, which makes up 35% of all new cases of dialysis worldwide as they endure a decrease in their quality of life following the initiation of chronic hemodialysis treatment. Because of advancements in nanotechnology, anti-diabetic drugs can be attached, deconstructed, incorporated, encapsulated, or connected to nanoparticles (NPs) in a system known as a Nano platform drug delivery system. Unlike traditional DN treatments, drug delivery using nano platforms allows for precise medicine distribution to kidney regions while also interfering with other biological processes. For the diagnosis of DN, over time intervention as well as security evaluations using in vitro and In vivo studies would be required for this successful clinical implementation of the emerging pattern of multifunctional targeted NPs. Modified drug-loaded nanoparticles during advancements in nanoparticle therapeutics for DN in order to conform to the directional characteristics of the disease processes. Hence, the development of nano-drug delivery technologies, which also improve pharmaceutical effectiveness and safety, brings potentially new focused therapeutic possibilities to treat individuals with DN.